Mitochondrial Regulation of Macrophage Response Against Pathogens - Choudhuri, Subhadip; Chowdhury, Imran Hussain; Garg, Nisha Jain (Frontiers in Immunology, 2021)
Innate immune cells play the first line of defense against pathogens. Phagocytosis or invasion by pathogens can affect mitochondrial metabolism in macrophages by diverse mechanisms and shape the macrophage response (proinflammatory vs. immunomodulatory) against pathogens. Besides NADPH oxidase, mitochondrial electron transport chain complexes release superoxide for direct killing of the pathogen. Mitochondria that are injured are removed by mitophagy, and this process can be critical for regulating macrophage activation. For example, impaired mitophagy can result in cytosolic leakage of mitochondrial DNA (mtDNA) that can lead to activation of cGAS-STING signaling pathway of macrophage proinflammatory response. In this review, we will discuss how metabolism, mtDNA, mitophagy and cGAS-STING pathway shape the macrophage response to infectious agents.